Nature, Nurture And Universal Grammar. - Crain, Stephen; Pietroski, Paul (Linguistics & Philosophy, 2001)
In just a few years, children achieve a stable state of linguistic competence, making them effectively adults with respect to: understanding novel sentences, discerning relations of paraphrase and entailment, acceptability judgments, etc. One familiar account of the language acquisition process treats it as an induction problem of the sort that arises in any domain where the knowledge achieved is logically underdetermined by experience. This view highlights the 'cues' that are available in the input to children, as well as children's skills in extracting relevant information and forming generalizations on the basis of the data they receive. Nativists, on the other hand, contend that language-learners project beyond their experience in ways that the input does not even suggest. Instead of viewing language acqusition as a special case of theory induction, nativists posit a Universal Grammar, with innately specified linguistic principles of grammar formation. The `nature versus nurture' debate continues, as various ``poverty of stimulus'' arguments are challenged or supported by developments in linguistic theory and by findings from psycholinguistic investigations of child language. In light of some recent challenges to nativism, we rehearse old poverty-of stimulus arguments, and supplement them by drawing on more recent work in linguistic theory and studies of child language.